Pelatihan dan Pendampingan Penulisan Karya Tulis Ilmiah untuk Peningkatan Profesionalisme Guru SD di Kota Malang - Cholifah, Puri Selfi; Nuraini, Ni Luh Sakinah; Rini, Titis Angga (Universitas Nusantara PGRI Kediri, 2024)
Common problems include teachers having difficulty carrying out classroom action research activities and also having difficulty writing scientific articles. This problem has an impact on other problems, namely efforts to continue seeking promotion with work that is not original. Based on the problems that occur in partner schools, an alternative solution is offered, namely providing assistance in writing scientific papers for elementary school teachers in Malang City. In this activity, almost all participants fully participated in the activities that had been carried out and were also involved in submitting the final assignment. In the majority, the final assignments submitted are draft articles based on IMRAD style journals. Based on the results of the review of assignments that have been developed, as many as 15 work titles are in the journal review stage to be ready for publication. This shows the success of the activities carried out.